Pengaruh Suhu Kalsinasi Sekam Padi Terhadap Produksi Silika (SiO2) - Althof, Hasna Sausan; Beri, Deski (Periodic, 2024)
Rice husk is a leftover material from the rice milling process and is known to have a high silica (SiO2) content. In this study, rice husk was calcined with temperature variations of 800℃, 850℃, and 900℃ to see the effect on the ash content produced. The ash obtained becomes whiter as the calcination temperature increases. The darker ash color indicates that there is still carbon content. In this study, silica was extracted using NaOH 10% and precipitated with HCl 10%. The synthesized silica was characterized using XRF. The results of the analysis using XRF revealed that the optimum calcination temperature was obtained at 900℃ which produced the highest silica yield of 96.32% with silica purity (SiO2) reaching 70.307%.